Geospatial Analysis of Ayurveda Healthcare Facilities in Kathmandu Valley, Nepal - Nirmal Bhusal,; Sah, Mithilesh Kumar; Munkarna Thapa,; Thakur, Santosh Kumar; Rupendra Maharjan,; Birat Shrestha,; Bikas Raj Ghimire,; Pradeep KC,; Vasudev Upadhaya, (Journal of Ayurveda Campus, 2025)
Background: Ayurveda plays a vital role in Nepal’s health care delivery system. Despite its cultural importance, the geographical accessibility and distribution of Ayurveda health centers remain underexplored. This study aimed to map and analyze the spatial distribution of Ayurveda health centers in Kathmandu Valley using Geographic Information Systems (GIS) and mobile-based data collection tools.Materials and Methods: The mixed-methods geospatial research was conducted in three districts of Kathmandu Valley- Kathmandu, Lalitpur, and Bhaktapur. Data were collected from 267 Ayurveda health centers by trained surveyors using the SW-Map mobile application, supplemented by hardcopy forms. The collected geospatial data were processed using ArcGIS 10.7.1 to analyze distribution and accessibility patterns. Visualization was performed on Google Earth, with outputs generated in KML format.Results and Discussion: A total of 267 clinics were identified: 221 (82.8%) in Kathmandu, 20 (7.5%) in Lalitpur, and 26 (9.7%) in Bhaktapur. Spatial analysis showed a dense concentration in urban cores, with Kathmandu Metropolitan exhibiting the highest clustering. Accessibility analysis indicated that urban residents generally had a clinic within 2 km, while rural and peripheral populations often had to travel over 5 km. Services offered included Panchakarma, herbal medicine dispensing, yoga, massage, and diagnostics.Conclusion: GIS proved effective in mapping Ayurveda health centers and identifying accessibility gaps. The study highlights inequitable distribution, with underserved rural and peri-urban populations facing limited access. Findings can inform health policymakers to expand Ayurveda services strategically